X ANALYTICAL AND EXPERIMENTAL MODEL FOR ASSESSING THE DEPRECIATION RATE OF TRANSFORMER OIL BASED ON PHYSICOCHEMICAL FACTORS - Usmonov, Dilmurod; Kutbidinov, Odiljon; Abdullabekov, Dilafruz; Xushbaqov, Mirzohid (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article covers methods for determining experimental coefficients in a reliability model based on the physicochemical parameters of transformer oil. In the developed mathematical model, the influence of such factors as humidity, oxygen content, acid number, dielectric breakdown voltage, and oxidation products on the aging rate is assessed on a statistical basis. Modeling is carried out using the OLS (Least Squares Method). This approach is important in assessing the technical condition of the transformer.